(3aJM GdbQjH GdeLjH Ydi GdJQZjH hGdJQgjHs - (3MSf Hf YdjGdajhej GdbGgQj, CHh Ydj,J (B870 (3g` s
(3ChdgG (B:s
(3cJGH GdLgGO , GdJQZjH ai GdQHGW ai SHjd Gddg YR hLd hjHOC Hbhdg (B: (3Yf Sgd Hf SYO GdSGYOi bhdg Udi Gddg Ydjg hSde QHGW jhe ai SHjd Gddg NjQ ef GdOfjG heG ajgG s
(3BNQgG (B:s
(3BNQ GdehLhO efg CKfGA GdcdGe ai GdJQZjH ai GdQMdI ai WdH GdYde HGdMOjK GdTQja (B: (3EPG GSJjbX CMOce ef fheg adG jZeS jOg ai GdEfGA MJi jZSdgG aEfg dGjOQi Cjf cGfJ jOg GdMOjK s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jhLO HgPG GdLRA HjGV bdjd s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs